Intakes of Vitamin a and Zinc and Markers of Oxidative Stress in Newly Diagnosed HIV-positive Participants in the MASH Cohort in Miami (P24-016-19). (13th June 2019) - Clayton, Priscilla; Campa, Adriana; Liu, Qingyun; Martinez, Sabrina; Seminario, Leslie; Jasmin, Juphshy; Hernandez, Jacqueline; Teeman, Colby; Tamargo, Javier; Huang, Yongjun; Zarini, Gustavo; Baum, Marianna
Abstract: Objectives: HIV infection is characterized by increased oxidative stress. We examined the association of antioxidant intake with measures of oxidative stress and HIV disease progression in newly diagnosed HIV-infected participants. Methods: Cross-sectional study of 52 newly-diagnosed HIV-positive participants in the MASH cohort. Blood was drawn for parameters of oxidative stress (oxidized glutathione % and oxidative mitochondrial DNA damage [8-oxo-dG]) and disease stage (CD4- cell counts; HIV-viral load). Questionnaires on demographics and 24-hour dietary recalls and Alcohol Use Disorders Identification Test (AUDIT) were administered. AUDIT scores ≥ 8 was considered hazardous drinking. Dietary intakes of vitamin A and Zinc were calculated. SPSS was used for analyses and Linear Regression Models were estimated. Results: Participants were 74% male, 75% Black Non-Hispanic, and 21% Hispanics. Mean age was 42.3 ± SD10.2 years, CD4 count was 506.7 ± SD733.4 cells/µLA cross-sectional and HIV viral load was 3.63 ± SD1.23log10 copies/mL. Dietary intake of vitamin A (β = −0.001, SE = 0.0002, P  = 0.044) and zinc (β = −0.0004, SE = 0.0002, P  = 0.044) were inversely related with mitochondrial DNA damage (8-oxo-dG), after adjusting for education, race, age, gender, and excessive alcohol use. Oxidized glutathione percentage was directly associated with HIV-viral load (β = 0.81, SE = 0.4, P  = 0.037) adjusting for age, gender, AUDIT ≥ 8 and BMI in linear regressions. Conclusions: Lower intake of vitamin A and Zinc were associated with higher oxidative stress and higher HIV viral load. These findings suggest that antioxidant supplementation may be beneficial immediately after receiving a diagnosis of HIV infection as well as during antiretroviral treatment. Funding Sources: Funded by the National Institute on Drug Abuse and the National Institute of Health.